Bis(2-pyridylimino)isoindolato iron(II) and cobalt(II) complexes: Structural chemistry and paramagnetic NMR spectroscopy - Kruck, Matthias; Sauer, Désirée C.; Enders, Markus; Wadepohl, Hubert; Gade, Lutz H. (Dalton transactions, 2011)
Condensation of phthalodinitrile and 2-amino-5,6,7,8-tetrahydroquinoline gave the bis(2-pyridylimino)isoindole protioligand 1 (thqbpiH) in high yield. Deprotonation of thqbpiH (1) using LDA in THF at −78 °C yields the corresponding lithium complex [Li(THF)(thqbpi)] (2) in which the lithium atom enforces almost planar arrangement of the tridentate ligand, with an additional molecule of THF coordinated to Li. Reaction of cobalt(II) chloride or iron(II) chloride with one equivalent of the lithium complex 2 in THF led to formation of the metal complexes [CoCl(THF)(thqbpi)] (3a) and [FeCl(THF)(thqbpi)] (3b). The paramagnetic susceptibility of 3a,b in solution was measured by the Evans method (3a: μeff = 4.17 μB; 3b: μeff = 5.57 μB). Stirring a solution of 1 and cobalt(II) acetate tetrahydrate in methanol yielded the cobalt(II) complex 4 which was also accessible by treatment of 3a with one equivalent of silver or thallium acetate in DMSO. Whereas 3a,b were found to be mononuclear in the solid state, the acetate complex 4 was found to be dinuclear, the two metal centres being linked by an almost symmetrically bridging acetate. For all transition metal complexes paramagnetic 1H as well as 13C NMR spectra were recorded at variable temperatures. The complete assignment of the paramagnetic NMR spectra was achieved by computation of the spin densities within the complexes using DFT. The proton NMR spectra of 3a and 3b displayed dynamic behaviour. This was attributed to the exchange of coordinating solvent molecules by an associative mechanism which was analysed using lineshape analysis (ΔS≠= −154 ± 25 J mol−1 K−1 for 3a and ΔS≠ = −168 ± 15 J mol−1 K−1 for 3b).